Has our long-term trip-making behavior changed due to COVID-19? - Khaled Hamad; Yahya El Traboulsi; Abdallah Shanableh; Rami Al-Ruzouq; Saleh Abu Dabous; Waleed Zeiada; Lubna Obaid (Archives of Transport)
This study investigates the impact of the COVID-19 pandemic on travel risk perceptions and shopping habits among individuals in the United Arab Emirates (UAE). The study's primary objectives are to analyze changes in travel risk perceptions and to examine shifts in travel behaviors and shopping patterns during and after the pandemic. A comprehensive survey was conducted, gathering data on socioeconomic demographics, travel risk perceptions, and shopping habits across three periods: pre-pandemic, during, and post-pandemic. The survey included a diverse and representative sample of UAE residents, covering various demographic factors such as gender, age, residency status, and emirate of residence. Data cleaning and pre-processing were employed to ensure the accuracy and reliability of the results. Descriptive analysis and statistical tests such as the Wilcoxon signed-rank test and One-way Analysis of Variance (ANOVA) revealed significant changes in perceptions and behaviors across the three periods. The findings indicate a notable decrease in travel risk perceptions post-pandemic, particularly concerning personal modes of transportation, including private vehicles, walking, and cycling, which were perceived as safer due to their ability to limit exposure. However, public transportation continued to evoke discomfort, reflecting ongoing concerns about virus transmission in crowded environments. The study also highlights changes in shopping behaviors, with a decline in in-person food and grocery shopping during the pandemic, as many individuals shifted towards online grocery delivery services for safety and convenience. Similarly, there was a reduction in in-person shopping for non-food items, accompanied by a significant increase in online shopping, indicating a broader shift towards e-commerce. Overall, these findings provide valuable insights for policymakers, businesses, and researchers, offering a deeper understanding of the lasting impacts of the pandemic on consumer behavior. The study underscores the need for strategies that address individuals' evolving needs and concerns in the post-pandemic era, promoting resilience and adaptability in both the travel and retail sectors.